(untitled) (American Journal of Islam and Society, 2003)
Founded in 1922 and moved to al-Haram al-Sharif in 1929, the Islamic Museum in Jerusalem houses artifacts covering nearly all oflslamic history and originating in North Africa, Turkey, Iran, Central Asia, and the Middle East. This beautifully illustrated volume, published with the support of UNESCO in both English and Arabic, treats a small part of the Museum’s collection: a selection of its Qur’an manuscripts. The work, divided into three parts, first introduces the Islamic Museum and its collection, then provides background information concerning relevant textual and art history, and finally presents 3 I Qur’an manuscripts in detail. Part One, "The Islamic Museum," gives an overview of the Museum’s holdings, including wood, metalwork, ceramics, glass, tex tiles, coins, stone inscriptions and architectural elements, and documents. Most of the artifacts are material salvaged from repairs to the haram area or objects from the endowments of the Aqsa mosque and madrasahs in Jerusalem, Nablus, and Hebron. The collection includes many exquisite pieces: Umayyad floral woodwork panels from the al-Aqsa Mosque, a striking glass mosque lamp of the Mamluk amir Tankiz from Hebron, and the salvaged remains of Nur al-Din’s pulpit, built in Aleppo in 564/1168 and brought to the Aqsa Mosque in 583/1187 by Salah al-Din after his conquest of Jerusalem. (Unfortunately, the ornate wooden pulpit was nearly destroyed by arson in I 969.) Part Two, "Background," treats Arabic calligraphy, illumination, bindings, and the textual history of the Qur’an. Kufic, an old, square script said to derive from stone inscriptions, is used for the text of the old est Qur’an manuscript in the collection and for headings and panels in later manuscripts. The bulk of the manuscripts are written in the more cursive Naskhi script, which became popular by the tenth century, and the similar but taller Thuluth and Muhaqqaq. A number of the collections manscripts from North Africa are written in Maghribi script, which derives from Kufic and differs significantly from the common eastern scripts. This volume allows the reader to view some stunning examples of illumination ...